Second Language Acquisition: A Scientometric Review - Ахмед Алдуа; Ахмед Ях’я Алмакроб; Сільвія Аллегретта (Психолінгвістика, 2025)
Aim. This study investigates the development of knowledge and major trends in the field of Second Language Acquisition (SLA) from 1947 to 2022, employing both scientometric and bibliometric approaches.